Fiscal Soundness and the Triangle of Stability - Florian Buck; Ludger Schuknecht (Credit and Capital Markets – Kredit und Kapital, 2017)
Average gross general government debt-to-GDP ratios in advanced economies have almost reached their highest levels since WWII. Moreover, growing fiscal risks emerge from adverse fiscal-financial linkages and aging societies. Policy-makers should take advantage of the current economic recovery and extraordinary measures by central banks to pursue growth-friendly fiscal consolidation, supported by comprehensive structural and financial sector reforms to improve the growth potential and reduce future fiscal liabilities. These are fundamental elements to enhance macroeconomic resilience and to pave the way for a timely exit from expansionary monetary policy. In case of EMU, a strict implementation of the EU"s fiscal and banking sector governance is essential. – – Solide Staatsfinanzen und das Stabilitätsdreieck Die Staatsschuldenquoten der Industrieländer sind gegenwärtig nahe ihrem historischen Höchststand in der Nachkriegszeit. Der Risikoverbund zwischen Finanzsystem und Staatsfinanzen sowie negative demografische Entwicklungen drohen zudem, künftige Staatsbudgets noch weiter zu belasten. Angesichtsdessen sollte eine vorausschauende Finanzpolitik die günstige konjunkturelle Erholungsphase und außergewöhnlichen geldpolitischen Maßnahmen der Notenbanken für einen wachstumsfreundlichen Schuldenabbau nutzen. Zusammen mit ambitionierten Strukturreformen stärkt dies das Wachstumspotential der Volkswirtschaften und baut damit fiskalische Risiken ab. All dies bleibt zentral, um die Widerstandsfähigkeit der Volkswirtschaften zu stützen und den Weg für einen zeitlich angemessenen Ausstieg aus der ultra-expansiven Geldpolitik zu ebnen. In der europäischen Währungsunion ist hierfür die strikte Anwendung des gemeinsamen Regelwerks notwendig.
Keywords: H3; H6; E6; 330; fiscal policies; public debt; macroeconomic stability